2009
DOI: 10.1152/ajpcell.00093.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microvascular endothelial cell Na/H exchange: evidence for the presence of NHE1 and NHE2 isoforms and regulation by arginine vasopressin

Abstract: Blood-brain barrier (BBB) Na transporters are essential for brain water and electrolyte homeostasis. However, they also contribute to edema formation during the early hours of ischemic stroke by increased transport of Na from blood into brain across an intact BBB. We previously showed that a luminal BBB Na-K-Cl cotransporter is stimulated by hypoxia, aglycemia, and AVP and that inhibition of the cotransporter by intravenous bumetanide significantly reduces edema and infarct in the rat middle cerebral artery oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
70
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 76 publications
13
70
0
Order By: Relevance
“…Several recent studies have provided evidence that NHE-1 is present in rat and bovine brain endothelial cells (Sipos et al, 2005;Lam et al, 2009 sabiporide (73.6 ± 3.07%, 64.0 ± 7.75% and 58.1 ± 7.87%, respectively) ( Fig. 2A).…”
Section: 2mentioning
confidence: 89%
“…Several recent studies have provided evidence that NHE-1 is present in rat and bovine brain endothelial cells (Sipos et al, 2005;Lam et al, 2009 sabiporide (73.6 ± 3.07%, 64.0 ± 7.75% and 58.1 ± 7.87%, respectively) ( Fig. 2A).…”
Section: 2mentioning
confidence: 89%
“…19 In addition, AVP seems to be involved in brain edema formation by stimulation of the V1a receptors and influencing blood-brain barrier sodium transporters. 20,21 V1a receptor activation might also involve platelet activation, 22 thereby additionally increasing the risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…To date, nine isoforms of NHE have been identified in different tissues (Lam et al, 2009). Experiments with isolated sheep rumen epithelial cells (RECs) have shown that the specific inhibitors HOE 694 and S3226 of NHE-1 and NHE-3, respectively, are able to inhibit an acid-induced pH i recovery in these cells (Schweigel et al, 2005).…”
Section: Electroneutral Namentioning
confidence: 99%